Viral Hepatitis: HBV-HCV co-infection - Ahmed, Syed Minhaj Uddin; Quazi Manjurul Haque ,; Kazi Shihab Uddin,; Md Zulfikar Ali, (KYAMC Journal, 2024)
Co-infection with HBV and HCV is a complex clinical existence which estimated prevalence is reported 0.7% to 16% worldwide. HCV superinfection is very common due to viral replication in HCV is more dominant over HBV. Most of the clinical studies reported that disease progression is faster in HBV and HCV co-infected patients in compare to those with mono-infection. Therefore, early diagnosis and proper treatment is important for withholding the disease progression. Here a case of 45 years old male with fever, anorexia, vomiting and mucus mixed stool. HBsAg and anti-HCV are positive. USG of whole abdomen suggesting chronic liver disease with chronic kidney disease. Endoscopy of upper GIT revealed grade III esophageal varices. There are no established guidelines for treatment of HBV-HCV co-infection. Only symptomatic treatment was given. KYAMC Journal Volume: 14, No: 03, October 2023: 178-180.